Long-term Clinical Outcomes of Hematopoietic Stem Cell Transplantation in Multiple Sclerosis. (23rd February 2021) - Boffa, Giacomo; Massacesi, Luca; Inglese, Matilde; Mariottini, Alice; Capobianco, Marco; Moiola, Lucia; Amato, Maria Pia; Cottone, Salvatore; Gualandi, Francesca; De Gobbi, Marco; Greco, Raffaella; Scimè, Rosanna; et al.
Abstract : Objective: To determine whether autologous hematopoietic stem cell transplantation (aHSCT) is able to induce durable disease remission in people with multiple sclerosis (MS), we analyzed the long-term outcomes after transplantation in a large cohort of patients with MS. Methods: To be included, a minimum dataset (consisting of age, MS phenotype, Expanded Disability Status Scale [EDSS] score at baseline, information on transplantation technology, and at least 1 follow-up visit after transplantation) was required. Results: Two hundred ten patients were included (relapsing-remitting [RR] MS 122 [58%]). Median baseline EDSS score was 6 (1–9); mean follow-up was 6.2 (±5.0) years. Among patients with RRMS, disability worsening–free survival (95% confidence interval [CI]) was 85.5% (76.9%–94.1%) at 5 years and 71.3% (57.8%–84.8%) at 10 years. In patients with progressive MS, disability worsening–free survival was 71.0% (59.4%–82.6%) and 57.2% (41.8%–72.7%) at 5 and 10 years, respectively. In patients with RRMS, EDSS significantly reduced after aHSCT ( p = 0.001; mean EDSS change per year −0.09 [95% CI −0.15% to −0.04%]). In patients with RRMS, the use of the BCNU+Etoposide+Ara-C+Melphalan (BEAM) + anti-thymocyte globulin (ATG) conditioning protocol was independently associated with a reduced risk of no evidence of disease activity 3 failure (hazard ratio 0.27 [95% CI 0.14–0.50], p < 0.001). Three patients died within 100 days from aHSCT (1.4%); no deaths occurred in patients transplanted after 2007. Conclusions: aHSCT prevents disability worsening in the majority of patients and induces durable improvement in disability in patients with RRMS. The BEAM + ATG conditioning protocol is associated with a more pronounced suppression of clinical relapses and MRI inflammatory activity. Classification of Evidence: This study provides Class IV evidence that for people with MS, aHSCT induces durable disease remission in most patients.